2015
DOI: 10.1103/physrevb.91.144422
|View full text |Cite
|
Sign up to set email alerts
|

Combined first-principles and thermodynamic approach toM-nitronyl nitroxide(M= Co, Mn) spin helices

Abstract: The properties of two molecular-based magnetic helices, composed of 3d metal Co and Mn ions bridged by Nitronyl Nitroxide radicals, are investigated by density functional calculations. Their peculiar and distinctive magnetic behavior is here elucidated by a thorough description of their magnetic, electronic, and anisotropy properties. Metal ions are antiferromagnetically coupled with the radicals, leading to a ferrimagnetically ordered ground state. A strong metal-radical exchange coupling is found, about 44 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 74 publications
(137 reference statements)
0
7
0
Order By: Relevance
“…Tight convergence criteria were selected to ensure that the results are well converged with respect to technical parameters. Scarrozza et al 18 were omitted. The two calculated model structures of 1_a and 2_a including two radicals and one Co II ion extracted from compounds 1 and 2, respectively, and the complete molecular structure of 3 are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tight convergence criteria were selected to ensure that the results are well converged with respect to technical parameters. Scarrozza et al 18 were omitted. The two calculated model structures of 1_a and 2_a including two radicals and one Co II ion extracted from compounds 1 and 2, respectively, and the complete molecular structure of 3 are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Picozzi et al 18 reported one cobalt-based SCM, CoPhOMe, which possesses uniaxial anisotropy with a D z of 46 K (32 cm −1 ) by DFT calculation. They deduced two equations to obtain Δ ξ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice however, canting phenomena are often encountered in 1D Ising compounds, leading to varying angles ±  between the easy-axes and the chain direction. It is the case for instance in the molecular compound Co(hfac)2-NITPhOMe [7] which is the archetype of the Single-Chain Magnets [8,9]; It was recently demonstrated that the noncollinearity among the local anisotropy axis compels to deeply reconsider the theoretical description of the spin dynamics in this material [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report synthesis and crystal structures and magnetic properties of two nitronyl nitroxide radicals { R 1 = 4′-methoxy-phenyl-4,4,5,5,-tetramethylimidazoline-1-oxyl-3-oxide (NNPhOMe) and R 2 = 2-(2′-thienyl)-4,4,5,5-tetramethylimidazoline 3-oxide 1-oxyl (NNT)}-based four metal complexes. The theoretical analysis of magnetic properties using density functional theory (DFT), quantum chemistry, thermodynamic calculations, and so forth is commonly used for calculating the exchange interactions and exchange-coupling constant. Different computational methods have been employed to elucidate the mechanism of spin–spin interaction, the magnitude of effective exchange integrals, and the nature of the participating spin-active MOs. , The influence of the used basis set was emphasized in some of the studies. The model systems were excerpts from various experimentally obtained nitronyl nitroxide-based complexes with transition metal ions, which contained or did not contain unpaired electrons.…”
Section: Introductionmentioning
confidence: 99%